(untitled) (Res Medica, 2014)
Letter We are often told, "You don’t know what it feels like." This is often true, to imagine the plight felt by someone facing the consequences of a terminal illness will more than stretch empathy. Edinburgh medics face a newer, more intense form of this human misery, a cohort of young, vital people, cornered by drug addiction and threatened by AIDS. We present here a moving letter sent to RES MEDICA by a local drug user with HIV.